2016
DOI: 10.1016/j.csite.2016.06.010
|View full text |Cite
|
Sign up to set email alerts
|

Latent energy storage: Melting process around heating cylinders

Abstract: A physical model to investigate the melting process around a multiple of heating cylinders in the presence of the natural convection has been carried out. A numerical code is developed using an unstructured finite-volume method and an enthalpy porosity technique to solve for natural convection coupled to solid-liquid phase change. It is found that during the melting process around the cylinders, natural convection circulation around each cylinder interacts with the other cylinders to influence the melt shape. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…C is a constant measuring the shape evaluation of the melting zone and ε is a very small value to avoid the zero division. For further details regarding the resolution method and phenomenon description, readers are referred to previous works [45][46][47][48][49]. The thermal properties of the used PCM (n-eicosane) are listed in Table 1 [50].…”
Section: Phase Change Formulationmentioning
confidence: 99%
“…C is a constant measuring the shape evaluation of the melting zone and ε is a very small value to avoid the zero division. For further details regarding the resolution method and phenomenon description, readers are referred to previous works [45][46][47][48][49]. The thermal properties of the used PCM (n-eicosane) are listed in Table 1 [50].…”
Section: Phase Change Formulationmentioning
confidence: 99%
“…Heat transfer in the phase change materials is complicated by the presence of a moving border. Many studies have been shown that, at the initial stage, conductive heat transfer dominates in the region, however, with the growth of the melt region, an intensive regime of natural convection develops [18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…Particularly, melting coupled with natural convection in enclosures containing a PCM has been the subject of many experimental and numerical studies due its wide area of interest in several fields such as passive cooling of electrical or electronic components, thermal insulation and latent energy storage [2,3]. The effectiveness of cooling devices using PCM integrated in electrical components depends on the melting speed of the PCM so that the latent heat plays its role rapidly but also over time [4]. However, there are few studies in the literature reports including fins integration of PCMs, which have significant potential to enhance the thermal performance of PCMs.…”
Section: Introductionmentioning
confidence: 99%